Sonographic appearance of an advanced invasive mole and associated metastatic thrombus in the inferior vena cava. Issue 2 (12th January 2012) - Okumura, Maria; Fushida, Koji; Pulcineli Vieira Francisco, Rossana; Schultz, Regina; Zugaib, Marcelo
Abstract We present a case of an advanced invasive mole with a metastatic thrombus in the inferior vena cava in which sonography clearly showed vesicles in the myometrium, ovaries, and metastatic thrombus leading to a diagnosis of invasive mole rather than choriocarcinoma. © 2012 Wiley Periodicals, Inc. J Clin Ultrasound, 2013.